2009
DOI: 10.1186/1746-1596-4-7
|View full text |Cite
|
Sign up to set email alerts
|

Is there any potential link among caspase-8, p-p38 MAPK and bcl-2 in clear cell renal cell carcinomas? A comparative immunohistochemical analysis with clinical connotations

Abstract: Background: Clear cell renal cell carcinomas (ccRCCs) constitute the most common renal carcinomas, characterized by a relatively aggressive clinical course. Thus, scientific research is targeting towards the identification of immunohistochemical and molecular markers that could be useful regarding diagnosis, appropriate therapy and prediction of prognosis. In the present study we assessed and correlated the expression of caspase-8, phosphorylated p38 mitogen-activated protein kinase (p-p38) and bcl-2 protein w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…Increased p38-MAPK and SPOP expression in primary culture indicates their role in tumour progression. These findings were found consistent with earlier results, wherein p-p38 expression was shown to be high in high grade of RCC 16 . High expression of SPOP in metastatic RCC compared to normal kidney tissue can be used for diagnosis of primary site by immunohistochemistry/RT-PCR of metastatic lesion 5 .…”
supporting
confidence: 83%
“…Increased p38-MAPK and SPOP expression in primary culture indicates their role in tumour progression. These findings were found consistent with earlier results, wherein p-p38 expression was shown to be high in high grade of RCC 16 . High expression of SPOP in metastatic RCC compared to normal kidney tissue can be used for diagnosis of primary site by immunohistochemistry/RT-PCR of metastatic lesion 5 .…”
supporting
confidence: 83%
“…Actually, low expression of caspase‐8 due to promoter methylation was shown to be associated with poor survival in neuroblastoma20 and medulloblastoma12 as well as relapse of glioblastoma multiforme 21. In clear cell renal cell, caspase‐8 expression is linked to Fuhrman's grade and survival 22. Interestingly, a recently described 6‐nucleotide insertion–deletion polymorphism in the CASP8 promoter leading to decreased caspase‐8 expression may be associated with reduced risk of developing many types of human cancers, including colorectal carcinoma, possibly because of increased T‐cell resistance to activation‐induced apoptosis by cancer cells 23…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that either ERK1/2 or p38 can phosphorylate HIF-1 [111][112][113], while inhibition of these two MAPKs was capable of blocking the expression of reporter genes of the HIF-1 activity [114]. More recently, the use of p38 as a potential biomarker of ccRCC, which correlates well with Fuhrman grade, has been proposed [115]. In short, there is noticeable evidence suggesting that MAPK signaling pathways may be critical in the biological effects of the HIF in ccRCC and that the activation of MAPK signaling pathways plays a crucial role in tumorigenesis, metastasis, and angiogenesis of RCC.…”
Section: Renal Tumorigenesismentioning
confidence: 99%